Characterization and Growth Optimization of a Novel Salt Resistant Pseudomonas putida Strain Zm Capable of Degrading Trichloroethylene by Cometabolism Under Aerobic Conditions - Zhang, X.; Xu, D. (Asian Journal of Chemistry, 2013)
A novel toluene-oxidizing strain capable of cometabolizing trichloroethylene was isolated and characterized. Combined with 16S rRNA sequence analysis, it was identified as Pseudomonas sp. It could grow with toluene as the sole carbon source. The analysis of the growth curve showed that Zm could reach the logarithmic phase within 8-10 h. Continuous sampling showed that toluene was exhausted within 1 d. Finally 29.1 % of trichloroethylene (50 mg/L) can be removed after incubation in mineral salt medium in the presence of 200 mg/L toluene for 3 d and 62.7 % for 7 d. The optimization of growth conditions was also conducted, the optimal growth conditions as the follows: carbon source toluene, at the concentration of 200-400 mg/L, medium pH 7, temperature 28 ºC and shaking speed 200 rpm. The tested strain Zm also showed substantial salt resistance including at 3.5 % NaCl concentration, indicating the potential application in bioremediation of coastal and marine trichloroethylene contaminants.